ESTIMATION OF THE MAIN FLIGHT-TECHNICAL CHARACTERISTICS OF THE UNMANNED PLANE M6-3T FOR CARRIAGE OF SMALL VALUABLE CARGOES - Matiychyk Мykhailo; Mykhatskyi, Oleksiy (Proceedings of National Aviation University (archive), 2020)
The paper is devoted to application of methods of estimations of flight technical characteristics of an unmanned aircraft M6-3T «Zhayvir» for the transport of small cargoes. The aircraft has small values of the Reynolds number which imposes certain restrictions on its FTC and creates difficulties during the adaptation of on-board automatics to the main stages of flight: take-off, cruise flight, maneuvering and landing. As all these stages are performed automatically, there was a need for a considerable amount of calculation and experimental work to specify the baseline factors entered into flight controller that affect the entire range of velocities and their limitations. The purpose of the research is to clarify the flight characteristics of the model of an unmanned transport aircraft M6-3T «Zhayvir» in automatic mode at the stages of flight. The results of calculations on the M6-3T project and interpretation of data of the on-board recorder have been applied. The article presents the results of comparison of calculated and experimental data for a wide range of characteristic speeds of the M6-3T aircraft. In the process of preparing automatic flights, the final values of the variables need to be adjusted taking into account the experimental values obtained from on-board recorder.